Lateral-Torsional Buckling of C-Beams with Varying Inertia. (February 2019) - Mascolo, I; Modano, M; Amendola, A; Fraternali, F
Abstract: The present work deals with a numerical study on the flexural-torsional buckling of a thin-walled beam with uniformly varying C-section. Approximate solutions to the examined problem are obtained through the Dirichlet variational method and the Rayleigh-Ritz discretization procedure. The presented results prove to be asymptotically convergent for increasing numbers of test functions. This convergence property highlights the technical utility of the proposed approach, on considering the difficulty of obtaining analytic solutions for buckling problems of thin-walled beams with non-uniform cross-section.